2006
DOI: 10.2135/cropsci2005.06-0117
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment for Transgenic Sorghum in Africa: Crop‐to‐Crop Gene Flow in Sorghum bicolor (L.) Moench

Abstract: A crop‐to‐crop gene flow risk assessment study was conducted with Sorghum bicolor subsp. bicolor to estimate the impact of transgenic sorghum in (South) Africa. The trial was conducted with a central sorghum field (30 × 30 m) with male fertile donor plants that was surrounded by eight arms planted with male sterile recipient plants at a distance of 13 to 158 m from the central field. Gene flow was relatively high within the first 40 m and relatively low beyond that distance, but gene flow was detected even at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 32 publications
6
30
2
1
Order By: Relevance
“…The importance of spatial distribution of genetically differentiated landraces in influencing mating system in sorghum was shown by Ellstrand and Foster (1983), who showed that population structure had a great impact on the apparent outcrossing rate, a stratified treatment (varieties in rows over the field) producing significantly lower outcrossing rates than an overdispersed treatment (varieties mixed in the field). Schmidt and Bothma (2006) showed that pollen flow in sorghum in experimental conditions was relatively high within the first 40 m and continued to be observable at low levels at distances up to 158 m. Two features of the spatial distribution of landraces at Wanté-the pattern of planting fields with mixed landraces, and the close proximity of fields with different collections of landraces-favour pollen flow. Little information exists for comparing these patterns with those in other traditional sorghum cultivation systems.…”
Section: How Are Landraces Maintained?mentioning
confidence: 92%
“…The importance of spatial distribution of genetically differentiated landraces in influencing mating system in sorghum was shown by Ellstrand and Foster (1983), who showed that population structure had a great impact on the apparent outcrossing rate, a stratified treatment (varieties in rows over the field) producing significantly lower outcrossing rates than an overdispersed treatment (varieties mixed in the field). Schmidt and Bothma (2006) showed that pollen flow in sorghum in experimental conditions was relatively high within the first 40 m and continued to be observable at low levels at distances up to 158 m. Two features of the spatial distribution of landraces at Wanté-the pattern of planting fields with mixed landraces, and the close proximity of fields with different collections of landraces-favour pollen flow. Little information exists for comparing these patterns with those in other traditional sorghum cultivation systems.…”
Section: How Are Landraces Maintained?mentioning
confidence: 92%
“…Pollination by wind can occur at a frequency of 0.06% at a distance of 158 m from the pollen source (Ellstrand and Foster 1983;Schmidt and Bothma 2006). Sudangrass (2n = 20) outcrosses with other sudangrass at a much higher rate (20-61%) than grain sorghum, possibly because sudangrass has a more open and branching panicle than grain sorghum (Pedersen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Pedersen et al (1998) reported an average outcrossing rate of 48% between cultivated sorghum and sudangrass (Sorghum bicolor ssp drummondii). In Africa, pollen flow from cultivated to wild-weedy sorghums was predicted to occur naturally at frequencies of 2.5% at a distance of 13m (Schmidt and Bothma 2006). Recent surveys in Ethiopia and Niger (Tesso et al 2008) and in Kenya (Mutegi et al 2009) showed that sorghum congeners are found intermixed with and adjacent to cultivated sorghum and that their flowering periods overlapped with that of the cultivated sorghum.…”
Section: Introductionmentioning
confidence: 99%
“…Tanksley and McCouch (1997) considered such regions as "genetic insurance" where alleles lost through domestication and modern breeding can be recovered by falling back on the crop wild relatives or ancestors. Thus, gene flow plays a role in structuring the genetic variability within and among populations and understanding its consequences can contribute to scientifically based risk assessment for managing agricultural systems, understanding evolutionary processes and designing in situ conservation measures for genetic resources and using these resources to secure current and future plant breeding programs as described in other studies (Schmidt and Bothma 2006;Mutegi et al 2009;Hokanson et al, 2010). Mutegi et al (2009) suggested that special efforts should be directed to record and map wild sorghum populations in Kenyan national parks, as a possible further evidence to estimate the extent and direction of historical and recent gene flow between cultivated and wild sorghum for contribution to the national genetic resource conservation policy.…”
Section: Introductionmentioning
confidence: 99%